“The Giant and the Dragon” - a street theatre play with giant puppets (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
This paper comes from research developed between 2011 and 2013 in the undergraduate course in Drama at the Federal University of Ouro Preto (UFOP), State of Minas Gerais, Brazil. Through the discipline "Scenic Creation Workshop A” oriented by Animation Theatre studies, the giant puppets street play O Gigante e o Dragão (The Giant and the Dragon) came about. Here, the main goal is to present the research and the processes that permeated the creation, the making and the theatrical experiment of this play and, above all, highlight how powerful it is to recycle, reuse and re-signify various materials, aiming at the creation of expressive languages.Keywords: Animation Theatre; Expression Materials; recycling; resignification; reuse.
Keywords: Animation Theatre; Expression Materials; recycling; resignification; reuse